TAX INCENTIVES AND INDUSTRIAL DEVELOPMENT IN BANGLADESH: AN EVALUATION OF POLICY IMPACT ON SECTORAL GROWTH - Chowdhury, Mohammad Munayem (International Journal of Research -GRANTHAALAYAH, 2019)
Tax incentives are tools used worldwide to enhance domestic and foreign investment and enhanced investment leads to expected economic growth. This study is an attempt to review the industrial policies and direct tax incentives of Bangladesh to have a deep insight on the congruence among them and also show some indirect impact of tax incentives on development through analyzing some fiscal and investment data. Content and document analysis method has been used to accomplish this study. Sources of data were the industrial policies, tax codes and economic surveys of Bangladesh and some scholarly articles. By reviewing some tax related aspects of industrial polices and existing direct tax incentives provided by the tax authority, it was found that incentives suggested by industrial policies and actually provided tax incentives are almost same and the changing pattern of priority sectors have been shifted to infrastructure, power and technology sectors. By observing some investment and GDP related data it is found that local private sector investments are dominant over FDI and the manufacturing sectors contribution to GDP are increasing and consistent in last 13 years.